The use of topical antiseptic solutions in the healing process of post-surgical skin wounds in dogs (Canis lupus familiaris) - Thomás Souza e Silva; Soke Gninlome Cedril Hounkonnou; Hiasmin Marcia de Souza Lima; Joana Luiza Crispiano Cunha Santos; Fábio de Souza Mendonça; Rinaldo Florencio-Silva; Ricardo dos Santos Simões; Fabrício Bezerra da Sá; Joaquim Evêncio-Neto (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To evaluate whether the effectiveness of topical antiseptic solutions in restoring skin continuity solutions is related to their antimicrobial action or to their action in maintaining moisture, in dogs undergoing elective surgeries. Methods: Forty dogs, 20 males and 20 females, underwent orchiectomy and oophorectomy, respectively. Thereafter, the animals were allocated into four groups (n = 5) and treated with different topical solutions: polyhexanide 0.1% (G1), chlorhexidine digluconate 0.05% (G2), povidone-iodine 0.1% (G3), and sodium chloride 0.9% (control). Macroscopically evaluation of wounds on days 1, 5, and 10 after procedures, and hematological parameters were performed. Data were subjected to statistical analysis (p 0.05) Results: No significant differences in the macroscopic evaluation of the wounds and hematological parameters were observed among groups, in the healing of clean elective surgical wounds. However, applying a topical solution dressing to maintain a moist wound promoted adequate tissue healing. Conclusion: In our experimental conditions, moisture provided by topical antiseptic solutions is an important factor compared to the antiseptic activity of these solutions, for skin wound healing in post-surgical dressings resulting from clean, short-term elective surgeries in male and female dogs. Moreover, the type of topical antiseptic solution used does not influence the development of post-surgical infection.